The Metabolizable Energy Value, Standardized Ileal Digestibility of Amino Acids in Soybean Meal, Soy Protein Concentrate and Fermented Soybean Meal, and the Application of These Products in Early-weaned Piglets - H. Y. Zhang; J. Q. Yi; X. S. Piao; P. F. Li; Z. K. Zeng; D. Wang; L. Liu; G. Q. Wang; X. Han (Asian-Australasian Journal of Animal Sciences, 2013)
Three experiments were conducted to evaluate the metabolizable energy (ME) value, standardized ileal digestibility (SID) of amino acids (AA) of soybean meal (SBM), soy protein concentrate (SPC) and fermented soybean meal (FSBM), and the application of these products in early-weaned piglets. In Exp. 1, four barrows with initial body weight (BW) of 14.2±1.4 kg were used in a 4×4 Latin square design. The diet 1 contained corn as the only energy source. The other three diets replaced 25% of corn in diet 1 with one of the three soybean products, and the digestable energy (DE) and ME contents were determined by difference. In Exp. 2, four barrows (initial BW of 18.2±1.5 kg) were fitted with ileal T-cannulas and allotted to a 4×4 Latin square design. Three cornstarch-based diets were formulated using each of the soybean products as the sole source of AA. A nitrogen-free diet was also formulated to measure endogenous losses of AA. In Exp. 3, ninety six piglets (initial BW of 5.6±0.9 kg) weaned at 21±2 d were blocked by weight and assigned to one of three treatments for a 21-d growth performance study. The control diet was based on corn and SBM, the two treatments’ diets contained either 10% SPC or FSBM and were formulated to same SID lysine to ME ratio of 3.6 g/Mcal. The results showed that the ME content of SPC was greater than SBM (p<0.05). The SID of most AA in SPC was greater than the SID of AA in SBM (p<0.05). For the essential AA, the SID of histidine, isoleucine, leucine, lysine and threonine in FSBM were greater than in SBM (p<0.05). Even though they were fed same SID lysine to ME ratio of 3.6 g/Mcal diets, pigs fed SPC and FSBM diets had greater weight gain, G:F (p<0.05) and better fecal score (p<0.05) than pigs fed SBM diet. In conclusion, SPC showed a higher ME content and SID of AA than the SBM. SID of some essential AA in FSBM was higher than SBM and was similar with SPC. But the lower antigenic proteins and anti-nutritional factors content in SPC and FSBM may be the main factors affecting the performance of early-weaned piglets rather than the increased ME content and SID of AA.